Situation Report: Poland, 17 July 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Brandt's Visit to Rome and Church Administration in the Western and Northern Territories of Poland Closer Co-operation between Ministries Decisions on Development of Research New Deputy Chairman of the Supreme Chamber of State Control Polish-Austrian Compensation Treaty